2021
DOI: 10.1002/hbe2.310
|View full text |Cite
|
Sign up to set email alerts
|

Affordances of augmented reality technology for science education: Views of secondary school students and science teachers

Abstract: Using augmented reality (AR) in science education is one of the popular topics that have been researched in recent years. However, more qualitative studies are needed as the contributions of using AR in science education to the learning experience and knowledge construction can be better understood through qualitative research. Therefore, it is important to examine the opinions of teachers and students using AR on their experiences. This study aims to reveal their views on AR technology in terms of their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 77 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…Conclusions about students' affective domain of learning in the context of AR have been drawn through interviews, written surveys, observations, and even EEG measurements. It has been found that students who learned with AR were more intensively engaged in classroom discussions [36,39,77,85,117,120,122,131], were more focused [10,54,78,110,117], showed more enjoyment and interest [10,36,43,46,54,62,68,75,83,85,89,105,112,115,117,119,131] and more often overcame prejudices against the course [36]. Additionally, in the study by Arici et al the teacher reported that students liked to learn within an AR environment because it reminded them of a game environment [36].…”
Section: Positive Effects On Affective Domain Of Learningmentioning
confidence: 96%
See 3 more Smart Citations
“…Conclusions about students' affective domain of learning in the context of AR have been drawn through interviews, written surveys, observations, and even EEG measurements. It has been found that students who learned with AR were more intensively engaged in classroom discussions [36,39,77,85,117,120,122,131], were more focused [10,54,78,110,117], showed more enjoyment and interest [10,36,43,46,54,62,68,75,83,85,89,105,112,115,117,119,131] and more often overcame prejudices against the course [36]. Additionally, in the study by Arici et al the teacher reported that students liked to learn within an AR environment because it reminded them of a game environment [36].…”
Section: Positive Effects On Affective Domain Of Learningmentioning
confidence: 96%
“…It has been found that students who learned with AR were more intensively engaged in classroom discussions [36,39,77,85,117,120,122,131], were more focused [10,54,78,110,117], showed more enjoyment and interest [10,36,43,46,54,62,68,75,83,85,89,105,112,115,117,119,131] and more often overcame prejudices against the course [36]. Additionally, in the study by Arici et al the teacher reported that students liked to learn within an AR environment because it reminded them of a game environment [36]. Some studies have reported students' prolonged motivation for learning based on their prior AR learning experience [122].…”
Section: Positive Effects On Affective Domain Of Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Meta's heavy involvement in the VR market hints at a plan to facilitate tele-copresent social interaction between physically distant users [34]. Moreover, with the recent relevance of telemediated education [35,36], mixed reality social situations are likely to become more ubiquitous [37,38], with substantive consequences for learning [39].…”
Section: Introductionmentioning
confidence: 99%